Pilot archaeobotanical analysis of the sediment the well 112 in Pyrgi, Santa Severa - Kodýdková, Kateřina; Beneš, Jaromír; Komárková, Veronika; Paclíková, Klára (Fabrizio Serra editore, 2013)
Environmental archaeology today can enrich archaeological research by substantial informational level. In case of Santa Severa studies one recent dataset mapping site potential of archaeobotanical analysis was published (Sussana 2013), concentrated on dry situation of the medieval period. In case of the well 112, dated archaeologically to the Etruscan period, first series of archaeobotanical study is presented here. Excavation discovered here a set of features, submerged today in the sea. Our analytical study that was undertaken during September 2013 highlights possibility of systematic studies of those features estimating their contribution in area of subsistence reconstruction, agricultural practice and paleoecology. First analytical work undertaken here is mapping archaeobotanical potential of the site and is focused on analysis of macro-remains.
Keywords: Etruscans, harbour, well, macro-remains, environment, subsistance, rice